Papillary thyroid carcinoma presenting as miliary nodules on chest roentgenogram in the paediatric setting: A case report. (2020) - Viljoen, Nandi; Hendricks, Marc; Panieri, Eugenio; Aldera, Alessandro Pietro
Highlights: Papillary thyroid carcinoma (PTC) is the most common carcinoma encountered in the paediatric setting. PTC often presents with advanced locoregional disease in children and pulmonary metastasis are seen in up to 46% of cases. Miliary nodules on chest roentgenogram may be caused by miliary tuberculosis but other causes including metastatic carcinoma should be considered. Abstract: Introduction: Papillary thyroid carcinoma (PTC) is the most common carcinoma to occur in childhood with a peak incidence between 11–17 years, and typically presents with advanced locoregional disease. Pulmonary metastases are seen in up to 46% of cases and should enter the differential diagnosis of miliary nodules seen on chest roentgenogram, even in regions where tuberculosis is endemic. Presentation of case: An 11-year-old male presented with a short history of cough, shortness of breath and constitutional symptoms. Examination revealed cervical lymphadenopathy and diffuse bilateral nodular infiltrates on the chest roentgenogram. Investigation for Mycobacterium tuberculosis was negative and this initiated biopsy of a cervical lymph node. Histopathological examination revealed metastatic PTC. Ultrasonography and magnetic resonance imaging (MRI) were performed for preoperative staging. The patient subsequently underwent total thyroidectomy with selective neck dissection. Discussion: There are several potential causes when dealing with miliary nodules on chest roentgenogram. Thorough interrogation of the clinical, radiological, pathological and microbiological data is required to arrive at the correct diagnosis. Postoperative adjuvant therapy with radioactive iodine is recommended in children with metastatic disease, but this should be restricted preferably to a single dose to avoid the complication of pulmonary fibrosis. Conclusion: This case highlights the differential diagnostic considerations of a patient presenting with constitutional symptoms and a miliary pattern on chest roentgenogram. Carcinomas are uncommon in children but should not be forgotten.